Shear-wave elastography for the assessment of liver fibrosis in liver transplant recipients treated for hepatitis C virus recurrence. Issue 1 (January 2018) - Korda, David; Lenard, Zsuzsanna M.; Gerlei, Zsuzsanna; Jakab, Zsuzsanna; Haboub-Sandil, Anita; Wagner, Laszlo; Varga, Marina; Cseprekal, Orsolya; Marton, Adrienn; Horvathy, Denes; Takacs, Szabolcs; Doros, Attila; et al.
Abstract : Objectives: Direct-acting antiviral agents have revolutionized hepatitis C therapy, and are also found to be effective in the liver transplant setting. The extent of liver fibrosis influences patient management and is used to monitor therapeutic effects. Shear-wave elastography (SWE) is a relatively new imaging-based method that has not yet been studied extensively in liver transplant patients. Our aim was to study the effect of direct-acting antivirals in heaptitis C recurrence on liver stiffness determined by SWE. Patients and methods: A total of 23 liver transplant patients with hepatitis C recurrence were enrolled in this prospective study. The patients underwent 24 weeks of ombitasvir/paritaprevir/ritonavir+dasabuvir±ribavirin combination therapy. Elastographic examinations, serological tests and laboratory tests were performed, and serum biomarkers of liver fibrosis were calculated the day before treatment (baseline) and at the end of the treatment. Results: All our patients became hepatitis C virus RNA negative by the end of the treatment. Median liver stiffness values decreased significantly after treatment compared with baseline (8.72±3.77 vs. 7.19±2.4 kPa; P <0.001). Among the studied laboratory values, a significant decrease was observed in the levels of alanine aminotransferase, aspartate aminotransferase and γ-glutamyltransferase, whereas international normalized ratio levels increased. Serum biomarkers, namely aspartate aminotransferase-to-platelet ratio index and Fibrosis-4, decreased significantly after treatment compared with baseline. Conclusion: In the present study, SWE was succesfully used to monitor the beneficial therapeutic effects of direct-acting antivirals in hepatitis C recurrence following liver transplantation. We believe that SWE is a useful noninvasive diagnostic tool in the follow-up of hepatitis C treatment in liver transplant patients.